Classificação da água de irrigação em uma área cultivada com fruticultura irrigada - Lima Júnior, Benjamim Carvalho; de Lima, Vera Lúcia Antunes; de Farias, Maria Sallydelândia Sobral; Dantas Neto, José [UNESP]; Guimarães, Jean Pereira; de Lima, Mayra Gislayne Melo; Alves, Aaron de Sousa (My University, 2017)
The present study aimed to classify the quality of irrigation water for the use in agriculture at farm Ponta da Serra in the municipality of Queimadas-PB. In the study the characteristics of the water in the level of salinity was carried out, analyzing Electrical Conductivity (CEa) and the Total Dissolved Solids (TDS), and performing the framework and classification according to Resolution No. 357 of March 17, 2005 CONAMA, as the preponderant use. Furthermore, the physical and chemical properties of the irrigation water were analyzed for classification according to categories proposed by Ayers and Westcot (1999) and Richards (1954).
Classification of irrigation water in a cultivated area with irrigated fruit growing
Keywords: Banana; Salinization; Water quality